Cooperative beamsteering in wireless sensor network based on backtracking search algorithm - Mohamed Nazri, Akmal Fazrin (2019)
The progressive development of Wireless Sensor Network (WSNs) contributes to many applications such as in the intelligent transport system (ITS), safety monitoring, military and in natural disasters prevention. In parallel to WSNs, the idea of internet of things (IoT) is developed where IoT can be defined as an interconnection between identifiable devices within the internet connection in sensing and monitoring processes. With recent growth in both size and power efficient computing, the concept of the ubiquitous WSN has aggressively emerged as an acknowledged research topic. As the capabilities of individual nodes in WSNs increase, so does the opportunity to perform more complicated tasks, such as cooperative beamsteering (CB). This CB manages to improve the range of communications and save precious battery power during the transmission. Therefore, this research proposes a meta-heuristic algorithm to organize node location in array arrangement. It is expected to effectively improve radiation beampattern fluctuations, exhibits lower complexity and less energy. From the simulation that has been done, it's observed that the proposed algorithm helps to reduce the side lobe level, thus better radiation beampattern is achieved.